Proses Pemerolehan Bahasa pada Anak - Muhammad Peri Syaprizal (LEMBAGA PENELITIAN DAN PENGABDIAN MASYARAKAT (LPPM) UNIKS, 2019)
This research is about the process of language acquisition which is limited to language acquisition in children. The purpose of this study is to describe and analyze the process of language acquisition in children aged 0-6 years. Data was taken using descriptive methods and by taking data from direct interviews with parents of children, with stages of data collection, data analysis, and presentation of the results of the analysis. The results obtained from this study concluded that the factors that influence language acquisition in children are: age factor, because when they were children it would be easier to acquire a second language; first language factor (mother), because the first language is very influential in other grammar; environmental factors, the environment is a very important factor for the acquisition of language in children because children aged 0-6 years will acquire a language that he often hears from the environment, especially the family, friends and society; biological and cognitive factors; children up to 6 years old biologically and cognitively are still developing, when acquiring languages ​​it is very often the addition and reduction of pronunciation of words, this is a natural thing and will improve over time until the child really becomes more mature and mature than biological and cognitive aspects. Keywords: Language acquisition, language acquisition factors in children, biological and cognitive.